2017
DOI: 10.31231/osf.io/mfs63
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical Foundations to Guide Mindfulness Meditation: A Path to Wisdom

Abstract: Mindfulness interventions are becoming increasingly popular across a wide variety of clinical and non-clinical settings where they are often employed to promote psychological well-being. Mindfulness in its original context presented in Buddhist practice is used to systematically understand one’s moment-to-moment experience, and to gradually develop self-knowledge and wisdom. Buddhist teachings describe wisdom as seeing things just as they are - a requisite for the complete freedom from suffering. In psycholo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 98 publications
(134 reference statements)
0
8
0
Order By: Relevance
“…James observed that “personal consciousness thought is always changing” and that it is “sensibly continuous” and as such comparable to a river or stream 17 . Similar analogies exist in early Buddhist scriptures, describing sensory experiences and mental events, such as feelings, perceptions and volitions, to flow in a constantly changing “mind stream” 18 . It remains a challenge to reliably capture the stream of consciousness, which would enable the study of the dynamics of continuous experiences, such as altered states of consciousness, flow states 19 , or the affective states associated with mental disorders 20 .…”
Section: Introductionmentioning
confidence: 71%
“…James observed that “personal consciousness thought is always changing” and that it is “sensibly continuous” and as such comparable to a river or stream 17 . Similar analogies exist in early Buddhist scriptures, describing sensory experiences and mental events, such as feelings, perceptions and volitions, to flow in a constantly changing “mind stream” 18 . It remains a challenge to reliably capture the stream of consciousness, which would enable the study of the dynamics of continuous experiences, such as altered states of consciousness, flow states 19 , or the affective states associated with mental disorders 20 .…”
Section: Introductionmentioning
confidence: 71%
“…a In this regard, our sensory experiences (i.e., seeing, hearing, olfactory, taste, and bodily/tactile experiences) happen only in the present moment, which is constantly becoming the past. 34 For example, for the reader, seeing this text in this paragraph happens in the present moment, and thinking about something one experienced through the five senses yesterday (past) or thoughts related to various tastes and smells one may experience during the next meal (future) involve thoughts in the present moment (see Box 1).…”
Section: The First-person Perspectivementioning
confidence: 99%
“…However, what was presented reveals that individuals' experiences from the first-person perspective can be understood as a system that only consists of constantly changing sensory experiences and mental a However, this fact may not be noticeable to most people. 34 events, where it is also possible to distinguish the present moment, the past, and the future.…”
Section: The First-person Perspectivementioning
confidence: 99%
“…The aggregate of wisdom that flows into moral commitment includes right speech (sammā vāccā), right action (sammā kammanta), and right livelihood (sammāājīva). Moral nature will naturally bring a commitment to right effort (sammā vāyāma), right mindfulness (sammā sati), and right concentration (sammā samādhi) (Karunamuni & Weerasekera, 2019).…”
Section: Basic Philosophy Of Buddhist Mindfulness Counselingmentioning
confidence: 99%